Automated theater rigging. (Architectural Record)
This article reports on an automated theater rigging system. The antiquated counterweight rigging system requires stagehands to manipulate rigging at dangerous heights and in unsafe situations. Vortek is an ADA-compliant floor-to-ceiling system that uses intuitive touch-screens and menus to allow a professional or student crew to control the entire technical operation of a show from a single position. The product is introduced by Hoffend & Sons Inc.